2004
DOI: 10.1002/ijc.20543
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant humanized anti‐insulin‐like growth factor receptor type I antibody (h7C10) enhances the antitumor activity of vinorelbine and anti‐epidermal growth factor receptor therapy against human cancer xenografts

Abstract: Interaction of insulin-like growth factor receptor I (IGF-IR) with its ligands has been reported to induce cell proliferation, transformation and blockade of cell apoptotic functions. IGF-IR is overexpressed on numerous tumor cell types and its blockade could be of importance for anti-cancer therapy. We have generated a hu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 58 publications
6
152
0
2
Order By: Relevance
“…The mechanism by which h7C10 affects both Ser473 and Thr308 phosphorylation of Akt, whereas aIR3 only affects Ser473 phosphorylation of Akt is not clear. h7C10 has displayed significant effects on blocking IGF-1R b chain and inhibiting phosphorylation of both b chain and IRS-1, whereas aIR3 failed to inhibit phosphorylation of b chain and IRS-1 (Goetsch et al, 2005). The difference of h7C10 and aIR3 may be related to different effects of h7C10 and aIR3 on the inhibition of Thr308 phosphorylation of Akt.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mechanism by which h7C10 affects both Ser473 and Thr308 phosphorylation of Akt, whereas aIR3 only affects Ser473 phosphorylation of Akt is not clear. h7C10 has displayed significant effects on blocking IGF-1R b chain and inhibiting phosphorylation of both b chain and IRS-1, whereas aIR3 failed to inhibit phosphorylation of b chain and IRS-1 (Goetsch et al, 2005). The difference of h7C10 and aIR3 may be related to different effects of h7C10 and aIR3 on the inhibition of Thr308 phosphorylation of Akt.…”
Section: Discussionmentioning
confidence: 95%
“…We therefore hypothesized that blockade of IGF-1R would prevent rapamycin-mediated Akt activation. As shown in Figure 5, 3 h of pretreatment with 1 mg/ml h7C10, a human monoclonal antibody against IGF-1R (Goetsch et al, 2005), resulted in abrogation of rapamycininduced Akt phosphorylation in both cell lines (Figure 5a). Pretreatment with 10 mg/ml h7C10 displayed an even more significant effect on the complete blockade of Akt activation induced by rapamycin (Figure 5b).…”
Section: Akt Activation Induced By Mtor Inhibition Is Igf-1r Dependentmentioning
confidence: 87%
“…Actually, one of the resistant cell lines (Line 2Res), originated from malignant melanoma, exhibited a >10-fold increased sensitivity to cisplatin and were >100-fold more sensitive to doxorubicin and mitomycin compared to parental cells. It is well known that the IGF-1R makes tumor cells more resistant to different types of cancer drugs and that attenuation of IGF-1R activity increases the efficiency of them (Jerome et al, 2003;Ye et al, 2003;Alexia et al, 2004;Goetsch et al, 2005). Apparently, this sensitizing effect of IGF-1R inhibition is not lost in PPP-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…These include agents that reduce ligand availability such as anti-IGF antibodies, anti-sense, and RNA interference molecules to reduce IGF-IR expression and small molecule inhibitors that target IGF-IR tyrosine kinase activity. Pre-clinical studies performed in vitro and/or in nude mice using these strategies have demonstrated that targeting IGF-IR directly or indirectly can inhibit breast cancer cell growth (Arteaga et al, 1989;Chernicky et al, 2000;Burtrum et al, 2003;Mitsiades et al, 2004;Goetsch et al, 2005;Divisova et al, 2006;Feng et al, 2006;Haluska et al, 2007;Rowinsky et al, 2007). Although these experiments certainly illustrate the therapeutic potential of inhibiting IGF-IR, there are a number of limitations of these studies that should be considered.…”
Section: Introductionmentioning
confidence: 99%